WIDE POSSIBILITIES OF USING INFORMATION COMMUNICATION TECHNOLOGIES IN TEACHING PHYSICS - Mufazzalshoh Alisher ugli Rakhmonov (Galaxy International Interdisciplinary Research Journal, 2022)
In this work, information is provided about the possibilities of using modern software tools in the physics classes of schools. The main focus is on factors necessary for students to expand their worldview and become deeply educated.